Influence of CFRP confinement on bond behavior of steel deformed bar embedded in concrete exposed to high temperature - Bengar, Habib Akbarzadeh; Hosseinpour, Mehdi; Celikag, Murude (Elsevier Science Inc, 2020)
The effectiveness of retrofitting with carbon-fiber-reinforced polymer (CFRP) wrapping for maintaining and improving the bond between steel rebars and heat-damaged concrete was extensively studied. Here, the effect of temperature (room temperature as the reference, 200, 400, 600, and 800 degrees C), concrete cover (25 mm and 35 mm), concrete compressive strength (30 and 40 MPa), and CFRP wrapping had on the concrete-rebar bond were investigated by conducting experiments. The results show that retrofitting with CFRP can not only significantly increase the bond strength of the specimens subjected to elevated temperatures, but also change the failure mode from brittle to a more ductile one, i.e., rebar pull-out failure. Moreover, the mechanical properties degraded as temperature increased, especially after 400 degrees C, such that at 800 degrees C, the compressive strength was reduced by about 80%. Exposure to heat reduced the concrete-rebar bond strength in the pull-out test specimens, and the level to bond strength reduction was less pronounced in the specimens with greater compressive strength and concrete cover. However, confinement with CFRP sheets significantly improved the bond strength, which was more considerable for the specimens exposed to higher temperatures. The effectiveness of CFRP wrapping was more significant for the specimens with a lower compressive strength and thinner concrete cover.
Keywords: Bond strength; Reinforced concrete; Deformed steel bars; High temperature; CFRP; Pull-out